The Adult Hip - Master Case Series and Techniques - Tsiridis, Eleftherios (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book is intended to offer a "virtual fellowship" in hip surgery that will give readers the opportunity to join distinguished hip surgeons in the operating room, learning key points and solutions to technical difficulties from the beginning to the end of 100 surgical cases. All of these cases have been carefully selected by renowned orthopaedists who work at the world's top centers and perform surgery based on evidence. To facilitate quick learning, the cases are presented using a uniform template, guiding the reader from clinical evaluation and preoperative planning, through the decision-making process, to the surgical procedure and the final outcome. At the end of each case, the editor invites the surgeon to answer specific questions in order to further elucidate crucial issues with reference to current evidence. The book is divided into four sections: conservative hip surgery, primary hip arthroplasty, complex hip arthroplasty, and revision arthroplasty. It will be of value across the world to specialist hip surgeons and surgeons in training who are interested in hip surgery.
Chapter 1. Hip arthroscopy- Surgical hip dislocation- PAO -- Chapter 3. Implant fixation -- Chapter 4. Resurfacing hip arthroplasty -- Chapter 5. Hip dysplasia acetabulum -- Chapter 6. Hip dysplasia femur -- Chapter 7. Varus / valgus -- chapter 8. Posttraumatic hip arthroplasty -- Chapter 9. THA following paediatric hip diseases Legg Perthes Calve - Slipped Capital Epiphysis -- Chapter 10. Osteonecrosis -- Chapter 11. Neurologic diseases - Parkinson disease -- Chapter 12. Haematologic disorders - Sickle cell anaemia -- Chapter 13. Ankylosis -- Chapter 14. Rheumatologic diseases - Paget disease -- Chapter 15. Autoimmune and inflammatory diseases -- Chapter 16. Ceramic on ceramic hip arthroplasty -- Chapter 17. Tumor excision -- Chapter 18. Impaction grafting socket -- Chapter 19. Acetabular augments and techniques -- Chapter 20. Cup cage technique - Distraction technique -- Chapter 21. Triflange -- Chapter 22. Cement in cement -- Chapter 23. Jumbo socket -- Chapter 24. Tantalum sockets -- Chapter 25. Recurrent dislocation -- Chapter 26. Dual mobility sockets -- Chapter 27. Reinforcements rings -- Chapter 28. Infection -- Chapter 29. Post resurfacing revision arthroplasty -- Chapter 30. Metal on metal revision -- Chapter 31. Trunnion disease -- Chapter 32. Acute and chronic hip dissociation -- Chapter 33. Impaction grafting femur -- Chapter 34. Cemented femoral revision -- Chapter 35. Cement in cement -- Chapter 36. Uncemented Femoral Revision. Cylindrical extensively porous coated; Titanium Fluted Tapered femoral stems -- Chapter 37. Total femoral replacement -- Chapter 38. Proximal femoral replacement -- Chapter 39. Periprosthetic fractures -- Chapter 40. Leng length discrepancy -- Chapter 41 Psychomotor Surgical Training in Virtual Reality. Panos Trahanias, George Papagiannakis, Kenanidis E., Eleftherios Tsiridis.
Description based on publisher-supplied MARC data.
Keywords: Orthopedics; Surgical Orthopedics